2017
DOI: 10.1002/ejic.201700546
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Boronic Acids: Acidity and Hydrolytic Stability of Fluorinated Phenylboronic Acids

Abstract: Abstract:The acidity constants and hydrolytic stability of all isomers of fluoro-substituted phenylboronic acids (F 1 -F 5 ) have been determined by both spectrophotometric and potentiometric methods. The introduction of fluorine into the aromatic ring enhances the Lewis acidity of boronic acids, depending on the position and number of fluorine substituents. Results of both methods show good agreement in most of the cases. To explain the observed discrepancies for several compounds, sta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Therefore the p K a values of compounds 1 and 2 have been determined by spectrophotometric methods and compared with the previously reported value for the para ‐isomer ( 3 ) . Similarly to other isomeric phenylboronic acids,, the position of the substituent influences the p K a value mostly for the meta isomer. In the case of the presence of the alkoxyl substituent (electron donating group) at the ortho ( 1 ) and para ( 3 ) positions a slight drop in acidity in comparison with the unsubstituted phenylboronic acid is observed.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore the p K a values of compounds 1 and 2 have been determined by spectrophotometric methods and compared with the previously reported value for the para ‐isomer ( 3 ) . Similarly to other isomeric phenylboronic acids,, the position of the substituent influences the p K a value mostly for the meta isomer. In the case of the presence of the alkoxyl substituent (electron donating group) at the ortho ( 1 ) and para ( 3 ) positions a slight drop in acidity in comparison with the unsubstituted phenylboronic acid is observed.…”
Section: Resultsmentioning
confidence: 96%
“…According to expectations, the acidity of meta ( 2 ) and para ( 3 ) isomers is higher than that for the unsubstituted phenylboronic acid: their p K a values are ca. one unit lower than that of a parent PhB(OH) 2 , which is 8.8 [ 3 ]. This is due to the inductive effect of the -OCF 3 group, which in comparison with the trifluoromethyl substituent (-CF 3 group) is slightly diminished by the resonance effect of an oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of a fluorine atom directly to the aromatic ring or to its substituents usually increases the Lewis acidity of these compounds, which is important in terms of their applications as well as stability [ 2 ]. The literature on arylboronic compounds with fluorine substituents is quite extensive and covers such areas as: acidity of the compounds [ 3 , 4 ], structural studies [ 5 , 6 , 7 ], NMR characterization [ 7 , 8 ], or equilibria in solutions [ 9 , 10 , 11 ] as well as antimicrobial activity [ 10 , 11 ]. The extreme electronegativity of the fluorine substituent induces a strong withdrawing inductive effect, whereas the resonance effect of its lone-pair electrons allows the fluorine atom to be considered as a π-electron donor as well [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benzoxaborole (2), 5-fluoro-substituted benzoxaborole (3) and 3-piperazine-bis(benzoxaborole) (4) were synthesized at the Faculty of Chemistry of Warsaw University of Technology by the research team of Prof. Agnieszka Adamczyk–Woźniak. Studies under aryl boronic acids stability showed that these compounds are stable under conditions of experiments (aquatic medium) [ 14 , 39 ].…”
Section: Methodsmentioning
confidence: 99%